Urine metabolomic characteristics of people exposed to hexavalent chromium in drinking water - Tao Yanan; Hu Miaomiao; Xia Yunting; Peng Fangda; Xiong Chuanlong; Ding Chunguang (Ecotoxicology and Environmental Safety)
This study investigated the toxicological mechanisms of hexavalent chromium (Cr(VI)) exposure on human health by analyzing the urinary metabolomics of residents exposed to Cr(VI) through drinking water. The aim of the study was to identify metabolites with significant differences and discover potential biomarkers for early detection and assessment of Cr(VI)-induced toxicity. Local residents aged 18–65 years were selected from both the Cr(VI)-exposed and control groups using simple random sampling. Using untargeted metabolomics technique, ultra-performance liquid chromatography coupled with quadrupole-time of flight mass spectrometry (UPLC-QTOF/MS) to detecte urine metabolites of people exposed to Cr(VI)in drinking water, combining multivariate and single-variable statistical analyses to screen different metabolites, and using MetaboAnalyst 5.0 software to conduct metabolic pathway analysis. 30 differential metabolites including Coproporphyrin Ⅲ, 7-Methylguanosine, Pentosidine, 18-Carboxy-dinor-LTE4, Deoxyguanosine, 4a-Hydroxytetrahydrobiop-terin, Dodecanediacylcarnitine, Allocholic acid, and Thromboxane were screened. Among these, 17 metabolites were up-regulated, such as Pentosidine, 18-Carboxy-dinor-LTE4, Dodecanediacylcarnitine, Allocholic acid, and Thromboxane, etc, while 13 metabolites were down-regulated, including Coproporphyrin III, 7-Methylguanosine, Deoxyguanosine, and 4a-Hydroxytetrahydrobiopterin, etc. N-ceramide-sphingosine, Stearic acid, Lysophosphatidylethanolamine (0:0/24:1), Lithocholic acid-3-O-glucuronide, (2E,4Z)-N-isobutyl-2,4-octadecanediamide, Thromboxane, Glycylcholic acid, and Pentosan were identified as potential biomarkers. Long-term exposure to Cr(VI) in drinking water might impact 13 metabolic pathways, including the urea cycle, androgen and estrogen metabolism, steroid synthesis, as well as arginine, proline, pyrimidine, and purine metabolism. Cr(VI) exposure might lead to damage of some metabolic pathways in drinking water and had potential health risks. Some ssential measures should be taken to reduce and prevent the intake of Cr(VI) from drinking water.